2006
DOI: 10.1128/jcm.01032-06
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Subgroups IIIA, IIIB, and IIIC Delineate Genetically Distinct Populations with Varied Pathogenic Potential

Abstract: Listeria monocytogenes lineage III strains belonging to subgroups IIIA (n ‫؍‬ 8), IIIB (n ‫؍‬ 5), and IIIC (n ‫؍‬ 6) were examined along with other known serotype strains (n ‫؍‬ 11) by PCR and Southern hybridization using several recently described species-, virulence-, and serotype-specific primers and probes. The virulence of seven representative lineage III strains was then evaluated in mice via the intraperitoneal route. The results suggest that subgroup IIIA consists of typical rhamnose-positive avirulent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 19 publications
5
72
0
4
Order By: Relevance
“…Phylogenetic analysis of VGC, LMO, and INL sequences confirmed previous reports (22,33,38) that lineage IV isolates are not part of a monophyletic lineage III and indicated that they represent an early divergence within L. monocytogenes (Fig. 2).…”
Section: Results Andsupporting
confidence: 69%
See 1 more Smart Citation
“…Phylogenetic analysis of VGC, LMO, and INL sequences confirmed previous reports (22,33,38) that lineage IV isolates are not part of a monophyletic lineage III and indicated that they represent an early divergence within L. monocytogenes (Fig. 2).…”
Section: Results Andsupporting
confidence: 69%
“…Toward that end, we recently described a singlewell DNA sequence-based subtyping method utilizing multilocus genotyping (MLGT) of single-nucleotide polymorphisms (SNPs) segregating within L. monocytogenes lineage I that provides high discriminatory power and good epidemiological concordance (5). While we previously focused on subtyping lineage I isolates because of their association with epidemic listeriosis, four major evolutionary lineages have been described for L. monocytogenes (22,33,36,38,46,47). L. monocytogenes isolates from lineage II are common contaminants of RTE and other food products (13,46), contribute significantly to sporadic listeriosis in humans (18), and include a previously described epidemic…”
mentioning
confidence: 99%
“…Lineage II isolates ( 1/2a, 1/2c and 3a serotypes) are more frequently isolated from foods and food environments compared to lineage I isolates (12,18). One of the isolates obtained from cheese samples in this study belonged to serotype 1/2a which is in agreement with previous studies in several countries (10,17).…”
Section: Discussionsupporting
confidence: 82%
“…Ninety six percent of the human cases of listeriosis are reported to be caused only by three serotypes among the 12 serotypes that are 1/2a, 1/2b and 4b. The other serotypes (especially 4a) are reported to be found mostly in foods and animals but rarely responsible for human L. monocytogenes infections (12).…”
Section: Introductionmentioning
confidence: 99%
“…Listeria monocytogenes encompasses a diversity of strains with various virulence and pathogenicity levels (10,19). Serovars 4b, 1/2a, and 1/2b account for the majority of human listeriosis cases, whereas other serovars, particularly serovar 4a, are rarely associated with listeriosis and are seldom isolated from foods (3,18).…”
mentioning
confidence: 99%